Population dynamics of the predator Alloeocranum biannulipes Montrouzier and Signoret (Hemiptera: Reduviidae) feeding on the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), infesting cassava chips - Loko, Y.L.E.; Onzo, A.; Datinon, B.; Akogninou, L.; Toffa, J.; Dannon, E.; Tamo, Manuele (Springer, 2020)
Functional and numerical responses of adult females of the predatory bug Alloeocranum biannulipes Montrouzier and Signoret (Hemiptera: Reduviidae) to density changes of the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae), infesting cassava chips were investigated under laboratory conditions. Starved predators were exposed to different prey density as treatments with 6 replicates. Numbers of prey consumed, eggs laid, and adults emerged as well as the hatching rates were recorded daily. When feeding on the larvae of P. truncatus, consumption increased linearly (R2 = 0.858) with the increase in larval density. At the highest pupal density of 6 P. truncatus pupae per predator, A. biannulipes adult showed the highest consumption rates (1.67 pupae). The Holling’s type I and III functional responses were observed when A. biannulipes consumed P. truncatus larvae and pupae, respectively. The attack of the predator estimated to 0.027 h−1 for larvae and 0.125 h−1 for pupae. The handling time spent on pupae by the adult predator was 0.352 h with a theoretical daily maximum predation (T/Th) of 68.18 pupae of P. truncatus. The numerical response of A. biannulipes was positively linked to pupal density, with more eggs laid per female, and higher hatching rate when exposed to higher prey densities. Efficiency of food conversion into eggs by A. biannulipes increased with decreasing larval densities and remained constant with increasing pupal densities. These functional and numerical responses exhibited by A. biannulipes suggest that this predator can effectively control P. truncatus larvae at low densities and pupae both at low and high densities. Therefore, A. biannulipes could be a good candidate for the biological control of P. truncatus